2005
DOI: 10.1111/j.1600-0404.2004.00356.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of motor and process skills reflects brain-injured patients' ability to resume independent living better than neuropsychological tests

Abstract: Assessment of motor and process skills reflects brain-injured patients' ability to resume independent living better than neuropsychological tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 20 publications
1
28
1
1
Order By: Relevance
“…Our study shows that direct observation of performance of activities assessed with the AMPS can provide additional relevant information about patients' functional ability problems, and may be helpful for a better understanding of these problems. In a study of recovery of specific cognitive functions and performance of daily life activities (determined with the AMPS) in severe brain-injured patients, Linden et al [15] concluded that the AMPS provides insight into a patient's rehabilitation different from that provided by cognitive tests and may be a better indicator of a patient's ability to resume independent living. Given the increased attention of occupational therapist interventions for people with dementia [21] , we feel that the AMPS can also be relevant for this population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study shows that direct observation of performance of activities assessed with the AMPS can provide additional relevant information about patients' functional ability problems, and may be helpful for a better understanding of these problems. In a study of recovery of specific cognitive functions and performance of daily life activities (determined with the AMPS) in severe brain-injured patients, Linden et al [15] concluded that the AMPS provides insight into a patient's rehabilitation different from that provided by cognitive tests and may be a better indicator of a patient's ability to resume independent living. Given the increased attention of occupational therapist interventions for people with dementia [21] , we feel that the AMPS can also be relevant for this population.…”
Section: Discussionmentioning
confidence: 99%
“…The AMPS has been used to assess the functioning of a variety of clinical populations, such as brain-injured patients [13][14][15] and psychiatric patients [16,17] . The instrument has also been studied in patients with dementia [18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%
“…Further details about the validity studies on each test are provided in many test manuals. For example, the AMPS has shown predictive validity for overall home safety (McNulty & Fisher, 2001), and increased prediction of independent living over neuropsychological tests (Lindén, Boschian, Eker, Schalén, & Nordström, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The AMPS offers a valuable alternative means of assessing IADL ability in ARBD, as it is widely used in occupational therapy practice and allows normative comparisons to be made. Evidence in the context of acquired brain injury and dementia suggests that the AMPS may predict an individual's capacity for independent living better than neuropsychological testing alone (Bouwens et al, 2008;Linden et al, 2005). Further research using the AMPS as an outcome measure for everyday functioning in ARBD is therefore recommended.…”
Section: Scores On the Amps Indicate That Participants Demonstrated Ementioning
confidence: 99%
“…The Assessment of Motor and Process Skills (AMPS; Fisher & Jones, 2012) is a standardised, norm-referenced occupational therapy assessment tool that uses observation to rate the quality of an individual's performance during IADL tasks. The AMPS has been used in traumatic brain injury and dementia research to provide insight into the functional difficulties individuals display as a result of cognitive impairment (Bouwens et al, 2008;Linden et al, 2005). The inclusion of the AMPS may therefore be advantageous in the comprehensive assessment of ARBD.…”
Section: Everyday Functioningmentioning
confidence: 99%